2022
DOI: 10.1002/jia2.26029
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous alcohol use and HIV indicators in six African countries: results from the Population‐based HIV Impact Assessments, 2015–2017

Abstract: Introduction: Hazardous alcohol use (HAU), defined as a pattern of alcohol consumption that increases the risk of harmful consequences for the user or others, is associated with an elevated risk of human immunodeficiency virus (HIV) infection and poor health outcomes. We describe the association between people living with HIV (PLHIV) who report HAU and key HIV indicators. Gaps in current literature in estimating HAU on HIV outcomes at the regional level of Eastern and Southern Africa still exist and our analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…We found no statistical evidence to support this in this study. This is similar to a study assessing alcohol consumption as a barrier to HIV testing in Uganda, which found it was not a barrier in men but was a potential barrier among women [45].This finding highlights a gap in research on whether being at risk of alcohol misuse is actually a barrier to use of SRH services by ABYM or whether it is the way services are provided not meeting the needs of those at risk of alcohol use [38,46,47].…”
Section: Plos Global Public Healthsupporting
confidence: 79%
See 1 more Smart Citation
“…We found no statistical evidence to support this in this study. This is similar to a study assessing alcohol consumption as a barrier to HIV testing in Uganda, which found it was not a barrier in men but was a potential barrier among women [45].This finding highlights a gap in research on whether being at risk of alcohol misuse is actually a barrier to use of SRH services by ABYM or whether it is the way services are provided not meeting the needs of those at risk of alcohol use [38,46,47].…”
Section: Plos Global Public Healthsupporting
confidence: 79%
“…On the other hand, despite almost a quarter of all study participants reporting being susceptible to peer pressure, we found no evidence of an association with not accessing services at hubs. This may suggest that while peers or other men may negatively influence sexual behaviours such as condom use, they could also positively influence access to HIV services, as was found in studies in Tanzania [35,38] and Zambia [39]. In addition, while most sexual behaviours in our study were not associated with accessing hub services, a higher percentage of ABYM who attended hubs tested for HIV and screened for STIs than those who didn't attend hubs, which could have been a result of accessing Yathu Yathu services.…”
Section: Plos Global Public Healthmentioning
confidence: 85%
“…Concordant with the emerging literature, where substance use burdens have been reported to be the highest among those aged 25 to 39 years and people living with HIV, concerns from the study population of young SMM (i.e., HIV epidemic priority population) regarding the frequency and quantity of peer substance use are validated ( Nouaman et al, 2018 ; Yaya & Bishwajit, 2019 ). Within the emerging literature, substance use has been associated with increased likelihood of sexual risk-taking behaviors, HIV transmission and acquisition, lower odds of viral suppression, and suboptimal outcomes along the HIV care continuum ( Chang et al, 2022 ; Daniels et al, 2018 ; Vinikoor et al, 2022 ). Emergent themes demonstrate the associations between stigma-induced substance use among SMM and high-risk sexual behaviors such as unprotected sex with STI prevalence and HIV infection ( Rogers et al, 2019 ; Stephenson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%